(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
The interaction of Fe(III) with niacin and pyridoxine was investigated by UV-Vis. spectrophotometry. The metal to ligand ratio for Fe(III)- niacin system was found to be approximately 1 : 3 and for Fe(III)-pyridoxine system it was 1 : 1. The redox properties of uncoordinated Fe(III)/Fe(II) system is reversible at platinum electrode and in presence of the ligands the system was found to be quasi-reversible in nature. It was also found that in every case the system was diffusion controlled. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21339 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 143-153, 2014